Life Skills-Based Life Therapy Program For Beneficiaries With Mental Disabilities - Rufran Zulkarnain; Ari Putra; Citra Dwi Palenti (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
Life skills education is carried out with the aim of providing skills to a person so that life becomes more productive and efficient. This study aims to describe the concept of learning life skills for people with mental disabilities at BRSPDM Dharma Guna Bengkulu which is packaged in a life therapy program. This study uses qualitative methods with data collection techniques used are interviews, observations, and documentation studies. Sources of information in this study are centered on social workers who serve people with mental disabilities. This is done to obtain information about life skills education programs for people with mental disabilities. The result of this research is a model of providing life skills to persons with disabilities by providing programs that are of interest to participants such as agriculture, fisheries, carpentry, local crafts, handicrafts, and hydroponic gardening. The learning process is carried out through identifying learning needs through interview techniques for each person with mental disability. Social workers have the task of formulating and identifying the required programs. So that, the life skills program is not only carried out within the Dharma Guna BRSPDM environment. Not only that, learning activities supported by partners can provide practical experience to learning participants with mental disabilities. The conclusion of this study is that livelihood therapy activities are a form of therapy-based learning that is able to provide provisions for people with mental disabilities. The identification process becomes the basis for providing navigation to learning participants both from directions to outcomes that can later be obtained by learning participants. Activities carried out individually on identifying learning needs are a way of receiving information about problems and future skill needs of people with mental disabilities.